Role of brain-derived neurotrophic factor in cognitive function and exercise - Mya Mya, Thwin; Aung Myo, Oo @mohd Hashym; Mohd Nasir, Mat Nor (Penerbit Universiti Sultan Zainal Abidin, 2020)
Brain-Derived Neurotrophic Factor (BDNF) is a member of neurotrophins and it plays important role in both peripheral nervous system (PNS) and short-term, as well as long-term plasticity in central nervous system. Physical exercise fosters neurocognitive functions and brain plasticity at all ages. However, there was an interesting finding stated that BDNF concentration was found to be lower in the trained athletes compared to that of control. Platelet BDNF is found to be acquired from the blood circulation rather than the megakaryocyte precursor cells. This review directs attention to the role of BDNF on cognitive function intensified by exercise for future perspectives.